Efficacy of focused shock-wave therapy in the treatment of chronic prostatitis / chronic pelvic pain syndrome in men - I. A. Labetov; G. V. Kovalev; O. V. Volkova; A. S. Shulgin; D. D. Shkarupa (Вестник урологии)
Introduction. Chronic prostatitis / Chronic pelvic pain syndrome (CP / CPPS) is an extremely common condition for which no effective treatment has been found yet. Focused shockwave therapy (fSWT) is a safe method of physical intervention that could potentially be effective in CP / CPPS treating.Objective. To evaluate the efficacy and quality of life of patients after treatment of CP / CPPS with fSWT.Materials and methods. A prospective cohort study included 48 patients diagnosed with CP / CPPS. The patients attended the clinic three times a week for 4 weeks (12 sessions). Each time, patients received fSWT therapy sessions by “Chronic pelvic pain” protocol. One month after the last therapy session, the men completed the validated NIH-CPSI, IPSS, and QoL questionnaires.Results. The mean age of the patients was 40 ± 9 years. After the course of therapy, the score of Domain I “Pain” from 10.0 ± 4.7 to 6.3 ± 1.9 (p < 0.001). At the same time, no statistically significant decrease was obtained in Domain II 'Urination' scores ((5,88 ± 2,40 vs 5,42 ± 1,64; p = 0,11). By the end of therapy for Domains III and IV, the scores had changed from 4.42 ± 0.90 and 4.04 ± 1.27 to 4.48 ± 1.01 and 3.08 ± 1.22, respectively (p < 0,001). It is noted that the mean IPSS questionnaire score showed no statistically significant change over the treatment period (17,2 ± 4,8 vs 17,8 ± 4,8; p = 0,074)). QoL changed from 4.48 ± 0.99 to 2.46 ± 1.03 (p < 0.001).Conclusion. The study demonstrated the efficacy of fSWT as a standalone method in the treatment of CP / CPPS.